Filosofia lean aplicada a casos de estudio, bajo la implementación del mampuesto cerámico (2018)
In the present monograph, case studies will be carried out on two construction projects that are immersed in the execution of an activity that involves the implementation of ceramic masonry. In these case studies, the level of applicability of three Lean Construction parameters will be evaluated; Reduction of time per activity, continuous improvement and Last Planner. With the final objective of proposing to the construction companies and the construction sector proposals for improvement through various methodologies that help to increase optimal levels of productivity